Chagas’ Disease: An Emergent Urban Zoonosis. The Caracas Valley (Venezuela) as an Epidemiological Model - Urdaneta-Morales, Servio (Frontiers in Public Health, 2014)
The unprecedented emergence of important public health and veterinary zoonoses is usually a result of exponential population growth and globalization of human activities. I characterized Chagas´ disease as an emergent zoonosis in the Caracas Valley (Venezuela) due to the following findings: the presence of reservoirs (Didelphis marsupialis, Rattus rattus) and vectors (Panstrongylus geniculatus, P. rufotuberculatus) infected with Trypanosoma cruzi in urbanized or marginalized areas; the elevated contact between P. geniculatus and humans detected by parasitological and molecular examinations of triatomine faeces demonstrated the possibility of transmission risks; a study of outbreaks of urban Chagas´ disease reported the first proven cases of oral transmission of T. cruzi to humans; the risk of transmission of glandular metacyclic stages from marsupials by experimental ocular and oral instillation; mice genitalia infected with T. cruzi contaminated blood resulted in the formation of amastigotes very close to the lumen suggesting that there may be a possibility of infection via their release into the urine and thence to the exterior; the ubiquitous histotropism and histopathology of T. cruzi was demonstrated using a mouse model; the presence of experimental T. cruzi pseudocysts in adipose, bone-cartilage and eye tissue indicated a potential risk for transplants. Socio-sanitary programs that include improvements in housing, vector control and access to medical treatment, as well as strategies aimed at combating social inequalities, poverty and underdevelopment should be undertaken in those areas where zoonoses are most prevalent. Disciplines such as Ecology, Epidemiology, Medical Entomology, Human and Veterinary Medicine, Environmental Studies, Public Health, Social and Political Studies, Immunology, Microbiology and Pharmacology, could all provide important contributions that aim to reduce the occurrence of factors governing the spread of emergent diseases.